Behavior of Malaysian iGeneration in purchasing life insurance policy / Nooriha Abdullah … [et al.] - Abdullah, Nooriha; Roslan, Azreen; Mohamed Yusuf, Rosmi Yuhasni; Mohd Rasid, Mohd Faizol Rizal (Faculty of Accountancy, 2018)
Globally the role of insurance industry is crucial for every country as it plays a core function in the mordern economy and the financial systems. Insurance/Takaful, like other financial services, has become important due to the increase of risks and uncertainties in most societies. Simultaneously, the rapid changes in technology has a huge impact on human lives, in particular the internet. Since iGeneration or commonly known as Generation Z, includes people born between 1990s and early 2000s, was born ‘in the internet’ era, therefore most of their decision to buy things depends on the info that is obtained from the internet. With less than 40 percent of Malaysian citizens that own a life insurance or family takaful policy, there is a significant, untapped potential for the insurance industry to penetrate Malaysian market in particular the iGeneration population. Hence, this paper is to determine the drivers of consumer purchase behavior that can influence the willingness of iGeneration to buy life insurance policy. Due to the characteristic of iGeneration, a survey via ‘google form’ was utilized in order to obtain the relevant data. Using quantitative research method, about 200 questionnaires were distributed. The research findings depict that variables of service quality of insurance company, perceived value of life insurance policy and role of agent were related with the dependent variable of iGeneration behavior. Subsequently, perceived value of life insurance policy was found to be the most influential factor that affects iGeneration behavior in purchasing life insurance policy. Thus, this paper suggests that iGeneration are aware about the benefits of purchasing life insurance products because iGeneration already have knowledge about life insurance policy and they can compare which insurance/Takaful products are more valuable and worth to purchase. The implication towards the insurance companies as a catalyst of financial system in Malaysia, should grab this opportunity to enhance their marketing efforts to capture the potential buyers among the iGeneration.